The Influence of Work Motivation And Perceptions of principal Leadershipto Performance of Junior High School Teachers In Pasir Sakti District East Lampung Regency - Muhammad Ihsan Dacholfany; Sunardi Sunardi; Ulwan Maghfur (At-Ta'dib, 2022)
The research population of 140 teachers using the Slovin formula , obtained a large sample of 58 teachers, while the steps for determining the sample were chosen randomly. Data collection in this study used a closed-type questionnaire instrument, namely by setting alternative answers for each statement item with the weight of the alternative sample answer scores determined by the researcher. The results of the analysis obtained in this study are as follows: (1) There is a positive influence between work motivation on teacher performance, this is explained by the regression equation = 66.586 + 0.084 X 1 so that it can be interpreted that any change in the score of the work motivation variable will result in an increase in teacher performance scores of 49.1%, (2) There is a positive influence between perceptions of principal leadership on teacher performance, this is explained by the regression equation = 56.507 + 0.413 X 2 so that it can be interpreted that any change in the score of the perception variable about leadership principals will result in an increase in teacher performance scores by 22.3%, and (3) There is a positive influence between work motivation and perceptions of principal leadership together on teacher performance, this is explained by the regression equation = 71.365 + 0.408 X 1 + 0.329 X 2 so that it can be indicated that the better work motivation and perception of Regarding the leadership of the principal, the better the contribution to the improvement of teacher performance with a significance value of 33.4%.